Immunology - Male, David K.; Brostoff, Jonathan; Roth, David B.; Roitt, Ivan M. (Elsevier/Saunders, 2013)
Immunology, 8th Edition makes it easy for you to learn all the basic and clinical concepts you need to know for your courses and USMLEs. This medical textbook's highly visual, carefully structured approach makes immunology simple to understand and remember. Understand the building blocks of the immune system - cells, organs and major receptor molecules - as well as initiation and actions of the immune response, especially in a clinical context. Visually grasp and retain difficult concepts easily thanks to a user-friendly color-coded format, key concept boxes, explanatory diagrams, and over 190 photos to help you visualize tissues and diseases. Put concepts into practice. Critical Thinking Boxes and 25 online cases encourage you to think immunologically while anchoring your understanding of immunology through clinical application. Gauge your mastery of the material and build confidence with high-yield style chapter-opening summaries and case-based and USMLE-style questions that provide effective chapter review and quick practice for your exams. Access the full contents online at www.studentconsult.com where you'll find the complete text and illustrations, USMLE-style questions, clinical cases, and much more! Get the depth of coverage you need in a smaller, more manageably sized book. Through meticulous editing and reorganization, primary material remains in the book while more specialized and clinical material has been moved online. Master the most cutting-edge concepts in immunology. Thorough updates throughout provide the timely knowledge you need ace your exams.